Transportation Arrangement as a Basic Plan for Politeknik Negeri Medan to Become an Environmentally Friendly Campus - Putri, Wirdatun Nafiah; Kusumadi; Oktaviani, Tetra; Ritonga, Efri Debby Ekinola; Anif, Bahrul (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
A green campus becomes one of the approaches to overcoming global warming. The green campus evaluation program currently being conducted by Universitas Indonesia is the UI GreenMetric World University Rankings, and one of the categories is transportation. One of the main contributors to pollution levels and carbon emissions is the transportation sector and is potentially to continue to rise unless sustainable prevention efforts are made. With its limited area, Politeknik Negeri Medan needs a more effective transportation arrangement to make it an environmentally friendly campus. Greenmetric assessments are conducted on existing conditions referring to the UI GreenMetric World University Rankings 2023 Guidelines with several criteria, namely the total number of vehicles (cars and motorcycles) divided by total campus population, shuttle services, zero emission vehicles (ZEV) policy on campus, the total number of zero emission vehicles (ZEV) divided by total campus population, ratio of ground parking area to total campus area, program to limit or decrease the parking area on campus for the last 3 years (from 2020 to 2022), number of initiatives to decrease private vehicles on campus, and pedestrian path on campus. The scoring result in the existing conditions is 725, or only about 40.3% of the total maximum value. GreenMetric scoring will increase to 1250 or 69.4% by implementing solutions for transportation arrangements in Politeknik Negeri Medan. The solutions are the use of access cards to filter unauthorized vehicles into the campus area, providing official vehicles electric cars and bicycles for use in the campus area, reducing the ground parking by making a vertical parking, utilizing buses as shuttle facilities for the academic community around the campus with a certain radius to reduce the use of private vehicles and supplementing existing pedestrian paths according to standards of safety, comfort and disability-friendly aspects by adding handrails, roof covers, directions, ramps for disabilities.